Economic regional and cross-border cooperation in the South-East Europe for the purpose of its faster integration in the European Union - Izet Ibreljic; Salih Kulenovic (European Regional Science Association (ERSA), 2004)
Territorial borders of the future European Union imply an integration of the South-East Europe into the EU political and economic structures. Such “map of the European Union” should represent the “European perspective” to the countries of the South-East Europe. At the present time, no-one can foresee when exactly shall countries of the South-East Europe join the EU, however the conditions that must be met are more-less well known and harmonized within the European Commission. Given the political and economic structure of the South-East Europe area, it is primarily “attractive market” for many European producers, as well as for future European investors. To achieve that, it is necessary to create the pre-conditions in the countries of the South-East Europe. Thus, it is necessary to intensify the regional cooperation between the countries in this region, wither by establishing the “classic free-trade zone” or by liberalization of trade through the network of bilateral contracts on free trade. The cross-border cooperation programs should link up all assistance that would be, for this purpose, coming from the EU. The primary goal of this paper is to research the possibilities and priority-areas of the economic-regional and cross-border cooperation in the South-East Europe in the context of its faster integration in the EU, as well as from the perspective of the optimal synchronization of this cooperation with political and economic strategy fo the EU toward these countries. As it is well known, re-unification of the continent is the joint goal of all citizens of the Europe. Key words: cooperation, South East Europe, European Union
Keywords: 330; cooperation; South East Europe; European Union